SELF-EVALUATION MODEL MANAGEMENT INCLUSIVE EDUCATION IN PRIMARY SCHOOL DISTRICT BANTUL YOGYAKARTA - Syamsi, Ibnu (Dewantara, 2014)
The research aims to find out the Self-Evaluation Model Management Inclusive Education in Elementary School Bantul Yogyakarta. Variables that will be revealed include: institutional, learning curriculum and evaluation, workforce, student affairs, infrastructure, and financing. Subjects were teachers, principals and committee inclusive education in primary school Bantul district. The total population was all Inclusive Elementary Schools located in Bantul district consisting both public and private elementary Inclusive schools.Type of evaluation research was the survey held in April-October 2013. The technique of collecting data included questionnaires: interview, observation, and documentation. Data analysis technique used integrated or simultaneous quantitative and qualitative descriptive approach.The results of the study revealed clearly and operational condition of the success of inclusive elementary schools, indicated by: (1) institutional, (2) curriculum, (3) staffing, (4) student, (5) infrastructure, and (6) financing, implementation and management success Inclusive Elementary School Principal in Bantul Yogyakarta.